How does mental fatigue affect soccer performance during small-sided games? A cognitive, tactical and physical approach - Kunrath, C. A.; Nakamura, F. Y.; Roca, A.; Tessitore, A.; Teoldo Da Costa, I. (Journal of Sports Sciences, 2020)
Objectives: We examine how mental fatigue (MF) influences peripheral perception, tactical behaviour, and physical performance of soccer players during a standardized small-sided game. Methods: Eighteen male university first-team soccer players participated. A modified Stroop task and the Vienna Test System were employed to induce MF and to evaluate players` peripheral perception, respectively. The FUT-SAT test was used to assess participants` tactical behaviour and physical performance was quantified using GPS technology. Results: MF decreased players` visual field (pre-test = 189.9° and post-test = 181.6°). Additionally, MF constrained players to more frequently perform actions related to the tactical principles of penetration, depth mobility, and defensive unity, and less frequently perform actions of defensive coverage and balance. During MF, players showed decreased accuracy in actions related to the principles of offensive coverage, width and length, offensive unity, delay, balance, concentration, and defensive unity. Finally, under MF players covered higher total distance and at more moderate speed. Conclusions: MF decreased players` peripheral perception, making them prioritize actions towards the opposing goal and protecting their own goal, while displaying more errors for most tactical actions. In summary, MF impaired several aspects of players` cognitive and tactical behaviours, causing a compensatory increase in physical performance.